2020
DOI: 10.1002/asia.202001179
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to Dispirocyclic Scaffolds Enabled by Diastereoselective Intramolecular Double Functionalization of Benzene Rings

Abstract: Here we describe the diastereoselective synthesis of (5r,8r)‐1,9‐diazadispiro[4.2.48.25]tetradecatrienes via domino double spirocyclization of N‐arylamide derivatives. This reaction can serve as a fast way to synthesize diazadispirocycles, which are found in the core structures of bioactive natural products. Product diversification via Suzuki–Miyaura cross coupling and application to the synthesis of 1‐oxa‐9‐azadispiro[4.2.48.25]tetradecatrienes were also conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Diazaspirocycles were synthesized by a diastereoselective double spirocyclization of N -arylamide derivatives in a dearomatization process (Scheme ). The use of HFIP as the solvent improved both the yield and the diastereo­selectivity of the reaction. Evaluation of different amine and amide substiutents indicated that the level of diastereoselectivity was heavily influenced by steric considerations and independent of electronic properties.…”
Section: Cyclization Reactionsmentioning
confidence: 99%
“…Diazaspirocycles were synthesized by a diastereoselective double spirocyclization of N -arylamide derivatives in a dearomatization process (Scheme ). The use of HFIP as the solvent improved both the yield and the diastereo­selectivity of the reaction. Evaluation of different amine and amide substiutents indicated that the level of diastereoselectivity was heavily influenced by steric considerations and independent of electronic properties.…”
Section: Cyclization Reactionsmentioning
confidence: 99%
“…Continuous efforts have been made to develop efficient methods for the construction of the spirocyclic structures . In particular, a strategy of spirocyclization through dearomatization, ipso -cyclization, has attracted much attention, providing these structures in short steps from easily available compounds . Although there has been significant progress in the synthesis of mono spirocycles with this direct strategy, the availability of di spirocyclic counterparts is relatively limited despite the high demand for a wide variety of spirocyclic structures. ,, To expand the diversity of the spiro compounds currently available, there is an urgent need to develop efficient synthetic methods to realize previously unexplored spirocyclic structures.…”
mentioning
confidence: 99%